Supernal Dreaming: On Myth and Metaphysics - Irwin, Lee (Religions, 2020)
The following article is an exploration of supernal dreaming, a type of dream that engages the dreamer as a profound, participatory, and often revelatory event. Dream types are not well developed in dream research; this article contributes to the development of a more typological approach to dream analysis. Four dream types are presented and contextualized with reference to their metaphysical and ontological significance. The types discussed are normative-rational dreams, mythic-imaginal dreams, psychic-intuitive dreams, and supernal-transpersonal dreams. The various types are illustrated with examples from the author’s extensive dream journal in order to highlight the subtle distinctions between the dream types, and how they might intersect or overlap. The dream morphology is placed within a larger context of metatheory based on the ontological significance of agency and its relationship, through dreaming, to a sentient cosmology. This cosmology is based on a creative, process-based metaphysics, in which dreams function to sustain and promote human development. Dreaming is presented as a visionary capacity leading to new enactive and embodied ways of life. The article shows how dreams can act as a stimulus for ontological insights and become a basis for paranormal perceptions and an inspirational approach to dream actualization.